METHODOLOGICAL AND METHODOLOGICAL FOUNDATIONS OF THE SOCIOLOGICAL STUDY OF ARCHIVES - Muydinova Mokhira Mukumjanovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article examines the methodological and methodological foundations of the sociological study of archives. The author tells the prospects of archival activities. The author tried to reveal the role of archives in the development of the state and the role of preserving the cultural heritage, the social memory of society. The article examines the development of archival activities in Uzbekistan.